Analysis of the structure and dynamics of labor cost in industrial enterprises from Ruse region - Dimitrova, Ivanka; Yankova, Diana (Leadership, Society, Strategic Visions, 2021)
Labor plays an important role in the functioning of the economy and its cost has economic and social dimensions. From the point of view of the enterprises, the labor cost is an expense (labor cost), and in terms of employees – employee income (salary). In this report, with the help of the structural and dynamic analysis, the level and the variation of the labor and wage costs, the comparisons in different cuts and the conclusions and proposals are formulated.